Pancreas Procurement and Preservation for Islet Transplantation: Personal Considerations - Hirofumi Noguchi (Journal of Transplantation)
Pancreatic islet transplantation is a promising option for the treatment of type 1 diabetic patients. After the successful demonstration of the Edmonton protocol, islet transplantation has advanced significantly on several fronts, including improved pancreas procurement and preservation systems. Since we frequently use pancreata from donors after cardiac death in Japan,we have applied the in situ regional organ cooling system for pancreas procurement to reduce the warm ischemic time. To reduce the apoptosis of pancreatic tissue during cold preservation, we have applied the ductal injection of preservation solution. For pancreas preservation, we use modified Kyoto solution, which is advantageous at trypsin inhibition and less collagenase inhibition. In this paper, we show pancreas procurement and preservation in our group for islet transplantation.